Thermal lag of the growth furnace heating assembly at CsI(Na) crystal growing fron constant melt volume on a seed - Goriletsky, V.I.; Vasilyev, V.V.; Sidletskiy, O.Ts.; Tymoshenko, M.M.; Sumin, V.I. (Functional Materials, 2007)
Thermal lag of the heater - crucible - crystal system has been determined at a large size CsI(Na) single crystal growing from constant melt volume on a seed. It has been established that during radial growth the temperature stabilization time at the bottom heater power variation is 1.3 times shorter than that at the size heater power variation. During axial growth, the time difference decreases, drops to 0 at cylinder height about 50 mm, and, then, reverses its sign.